Biotechnology annual review. - El-Gewely, M. Raafat (Biotechnology Annual Review., 1997)
This new series aims at covering the development in the field of biotechnology in the form of comprehensive, illustrated and well-referenced reviews. With the expansion in the field of biotechnology both in industry as well as in education, coupled with the increase in the number of new journals reporting new results in the field, the need for a publication that is continuously providing reviews is urgent. The goal of Biotechnology Annual Review is to fill this gap. Reviewed topics will include biotechnology applications in medicine, agriculture, marine biology, industry, bioremediation and the environment. Fundamental problems dealing with enhancing the technical knowledge encountering biotechnology utilization, regardless of the field of application, will be emphasized. Other issues, dealing with policy and regulation of biotechnology as well as the problems of development in developing countries, as related to biotechnology, will be included in the various issues. The "Editorial Board" of Biotechnology Annual Review encourages suggestions and contributions of articles from industry or from academic institutions that would constitute a comprehensive covering of a relevant topic in biotechnology